The Effect of Price Variables, Location Variables, and Promotion Variables on Consumer Decisions to Purchase Housing - Yusup Hari Subagya (STIE AAS Surakarta, 2021)
This research was conducted with the aim of knowing the effect of price variables, location variables, and promotional variables on consumer decisions in housing purchasing activities at PT. Gemilang. The method in this research is carried out using quantitative descriptive method with hypothesis testing, where the population in this study are all consumers who have made a purchase at PT. Gemilang, the sample of this study was 100 respondents. Sampling in this study using random sampling technique. The method used to collect research data using a questionnaire or questionnaire method, where testing of the results of the questionnaire in the study was carried out by validity analysis and reliability analysis. While the data analysis itself uses multiple regression analysis, t test, F test, R2 test. The results show that there is a significant influence between price variables on consumer decisions in housing purchases, there is a significant influence between location variables on consumer decisions in housing purchases, there is no significant influence between promotional variables on consumer decisions in housing purchases, and the three variables Simultaneously they have a significant effect on consumer decisions in purchasing housing.